Not everyone will be taken into the future - Bingham, Juliet (Tate Publishing, 2017)
Russian-born conceptual artists Ilya and Emilia Kabakov are among the most celebrated artists of their generation. Known for their pioneering large-scale environments and installations, the artists work fuses the everyday with the conceptual. Deeply rooted in the visual culture of Soviet society yet speaking equally to universal themes, their work is characterised by a sense of melancholia but also humour. Celebrating five decades of work, this book traces a line from Ilya Kabakov s early paintings, drawings, albums and installations to the collaborative projects made with his wife Emilia following his emigration to the West in 1987, which include immersive installations and architectural models
Published on the occasion of the exhibition Ilya and Emilia Kabakov : Not everyone will be taken into the future, Tate Modern, London, 18 October 2017 - 28 January 2018 ; The State hermitage Museum, St Petersburg, 20 April - 29 July 2018 ; The State Tretyakov Gallery, Moscow, 6 September 2018 - 13 January 2019
Keywords: Kabakova, Ėmilija -- 1945-; Kabakov, Ilʹja Iosifovič -- 1933-2023; Installation -- Kunst; Malerei; Zeichnung; Kabakov, Ilʹi͡a Iosifovich 1933- / Exhibitions; Kabakov, Emilia 1945- / Exhibitions; Kabakov, Ilya; Kabalov, Emilia; Art and Design; russisk kunst; Ausstellungskatalog -- Tate Modern -- 18.10.2017-28.01.2018 -- London; Ausstellungskatalog -- Gosudarstvennyj Ėrmitaž -- 20.04.2018-29.07.2018 -- Sankt Petersburg; Ausstellungskatalog -- Gosudarstvennaja Tretʹjakovskaja galereja -- 06.09.2018-13.01.2019 -- Moskau; Bildband